2022
DOI: 10.1002/jobm.202200473
|View full text |Cite
|
Sign up to set email alerts
|

Production of iturin A by Bacillus velezensis ND and its biological control characteristics

Abstract: Bacillus subtilis, as a biocontrol bacterium, possess a variety of biological functions and the capacity to control plant pathogens. Iturin A is a biosurfactant with broad‐spectrum antifungal activity produced by fermentation of B. subtilis. In this study, the dynamic parameters of solid‐state fermentation (SSF) and submerged fermentation (SMF) of Bacillus velezensis ND were compared, and a method for producing iturin A with a yield of 12.46 g/kg utilizing SSF was proposed. It has significant advantages over S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similarly, the results of this study showed that B. velezensis BHZ-29 bacteria and a sterile fermentation broth had a strong inhibitory effect on V. dahliae , and could significantly improve the agronomic traits such as plant height, root length and root weight of cotton seedlings. Similarly to the B. velezensis ND ( Tang et al, 2023 ), B. velezensis BHZ-29 has a strong biocontrol potential by inhibiting the growth of V. dahliae , activating the disease resistance of the cotton system, enhancing the resistance of cotton to Verticillium wilt, and increasing cotton yield.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the results of this study showed that B. velezensis BHZ-29 bacteria and a sterile fermentation broth had a strong inhibitory effect on V. dahliae , and could significantly improve the agronomic traits such as plant height, root length and root weight of cotton seedlings. Similarly to the B. velezensis ND ( Tang et al, 2023 ), B. velezensis BHZ-29 has a strong biocontrol potential by inhibiting the growth of V. dahliae , activating the disease resistance of the cotton system, enhancing the resistance of cotton to Verticillium wilt, and increasing cotton yield.…”
Section: Discussionmentioning
confidence: 99%
“…The biological functional studies of B . velezensis 504 were performed as previously reported studies ( Tang et al., 2023 ). We detected the siderophore production from B .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, beyond its antibacterial activity, iturin A has been reported to possess insecticidal and anticancer properties (Wan et al 2022). Its extensive application prospects in food, medicine, and agriculture have garnered signi cant attention from researchers (Tang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers primarily employ single-product fermentation methods for the production of iturin A and vitamin K2, which not only escalate production costs but also result in resource wastage. The fabrication methods of iturin A are predominantly divided into three categories: solid-state fermentation (SSF) (Khedher et al 2021), submerged fermentation (SMF) (Tang et al 2022), and two-compartment bio lm reactor fermentation (Tang et al 2023). Tang et al (Tang et al 2022)compared the kinetic parameters of solid-state fermentation (SSF) and liquid deep fermentation (SMF) of Bacillus subtilis natto spores and proposed an innovative method for producing iturin A, achieving a yield of 12.46 g/kg through solid-state fermentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation